School children to visit new art installation, March 7, 8 - Uribes, Tom::::::::: (2013)
A group of 5th and 6th grade students from Lindsay will visit Fresno State to view the massive willow branch sculpture created by internationally renowned artist Patrick Dougherty and several student and community volunteers last semester.